Lipid-based carriers for food ingredients delivery - Barroso, Livia (2021)
The encapsulation in the food industry has gained relevant importance, mainly due to its contribution to solve food problems by reducing the loss of nutrients, prolong the shelf-life, and improve food quality and safety. The lipid-based delivery systems as microemulsions, liposomes, solid lipid nanoparticles and nanostructured lipid carriers are widely used to deliver food ingredients due to their ability to protect and deliver it, enhancing its functionality and bioavailability. Despite the benefits on delivering food ingredients the toxicity profile of such carriers is usually neglected. The aim of this review is to provide a detailed overview on the application of lipid-based carriers to deliver food ingredients. Herein, the encapsulation advantages and disadvantages, and microencapsulation techniques used to obtain lipid-based carriers are discussed. More importantly, the different types of lipid-based carriers used for food ingredients delivery are thoroughly scrutinized, as well as their application in foods and possible toxicity concerns.